Open vs robot‐assisted radical cystectomy (BORARC): a double‐blinded, randomised feasibility study. (9th November 2021) - Maibom, Sophia L.; Røder, Martin A.; Aasvang, Eske K.; Rohrsted, Malene; Thind, Peter O.; Bagi, Per; Kistorp, Thomas; Poulsen, Alicia M.; Salling, Lisbeth N.; Kehlet, Henrik; Brasso, Klaus; Joensen, Ulla N.
Abstract : Objective: To examine surgical outcomes and feasibility of blinding patients and care providers to the surgical technique of radical cystectomy (RC). Patients and Methods: Single‐centre, parallel‐group, double‐blinded, randomised feasibility study of open RC (ORC) vs robot‐assisted RC with intracorporeal urinary diversion (iRARC) in an 'Enhanced Recovery After Surgery' setup. A total of 50 patients aged ≥18 years with bladder cancer planned for RC with an ileal conduit were included. Patients with previous major abdominal/pelvic surgery, pelvic radiation or anaesthesiological contraindications were excluded. Primary outcomes were proportion of unblinded patients and success of blinding using Bang's Blinding Index. Secondary outcomes included length of stay (LOS), complication rates, blood loss, pain, and opioid consumption. Results: A total of 26% of the patients were unblinded before discharge. We demonstrated that patients and doctors remained blinded for the allocated treatment, but nurses did not. Blood loss was greater in the ORC group as was operative time in the iRARC group. We found no difference in complication rate, LOS, or use of analgesics. Conclusions: The present study demonstrates that blinding of surgical technique in RC is possible. The results of secondary outcomes are consistent with the findings of previous unblinded randomised controlled trials. Our study highlights that it is possible to perform a blinded phase III study to explore the optimal surgical technique in RC.